Microdebrider Assisted Inferior Turbinoplasty: The Evaluation According to the Pathological Causes of Hypertrophied Turbinates (Medico Legal Update, 2021)
Background: Hypertrophied inferior turbinates are the frequent cause of nasal obstructions.Microdebridoris one of recent advances in technology used for reduction of hypertrophied turbinate to improve nasalbreathing.Objective: To evaluate and compare the effectiveness of microdedrider assisted inferior turbinoplasty onnasal breathing, turbinate size and complications according to the pathological causes.Patients and Method: Aprospective case study of 45 patients with chronic nasal obstruction andhypertrophied inferior turbinates underwent microdebrider assisted tubinoplasty. At Salah-eldeen GeneralHospital and private practice in salah-eldeen governorate, Iraq. During the peroid from June 2016-June2018. The patients were classified according to the cause of turbinate hypertophy and follow up at 1,3,and 12 months post operatievly for nasal bereathing and turbinate size.Results : The preoperative turbinatesize was grade III (48.5%) and grade IV (51.5%). At 1,3,and 12 months post operatively, the grade I andII was (87%). (90%), and (84%) respectively better in compensatory hypertrophy. The subjective patient’ssatisfaction grade I(relieved) and II(improved)) at 1,3, and 12 month after surgery was (100%) (97%) and(89%) respectively more satisfaction with compensatory hypertrophy.Conclusion: The therapeutic success of microdebrider turbinoplasty for improvement of nasal obstructionand turbinate size, according to the causes . In early postoperative period was almost equal,but long-termfollow-up (one year) found it was greater in compensatory hypertrophy and chronic rhinosinusitis andless in allergic and nonallergic rhinitis. There is no significant association between the cause of turbinatehypertrophy and type of complications.